Identifying innovations produced by primary health care centers and evaluating their scalability: the SPRINT Occitanie cross-sectional study in France - Alexis Vandeventer; Grégoire Mercier; Christophe Bonnel; Joana Pissarra; Grégory Ninot; François Carbonnel (BMC, 2024)
Abstract Background Practice-based research is one of the levers identified by the World Health Organization (WHO) to strengthen primary health care. The scaling of health and social care innovations has the potential to reduce inequities in health and to expand the benefits of effective innovations. It is now rapidly gaining the attention of decision-makers in health and social care, particularly in high-income countries. To meet the challenge of declining numbers of primary care physicians in France, Multi-professional Healthcare Centers (MHC) were created to bring together medical and paramedical professionals. They are a source of innovation in meeting the health challenges facing our populations. Specific methodology exists to identify health innovations and assess their scalability. A working group, including end-users and specialists, has adapted this methodology to the French context and the University department of general practice of Montpellier-Nîmes (France) launched a pilot study in Occitanie, a French region. Objective To identify and evaluate the scalability of innovations produced in pluri-professional healthcare centers in the Occitanie region. Methods A pilot, observational, cross-sectional study was carried out. The SPRINT Occitanie study was based on a questionnaire with two sections: MHC information and the modified Innovation Scalability Self-Administered Questionnaire (ISSaQ), version 2020. The study population was all 279 MHC in the Occitanie region. Results 19.3% (54) of MHC in the Occitanie region, responded fully or incompletely to the questionnaire. Four out of 5 U-MHCs were represented. Five MHC presented multiple innovations. The average per MHC was 1.94 (± 2.4) innovations. 26% of them (n = 9) had high scalability, 34% (n = 12) medium scalability and 40% (n = 14) low scalability. The main innovation represented (86%) were healthcare program, service, and tool. Conclusions In our cross-sectional study, a quarter of the innovations were highly scalable. We were able to demonstrate the importance of MHC teams in working on primary care research through the prism of innovations. Primary-care innovations must be detected, evaluated, and extracted to improve their impact on their healthcare system.